The mechanism of action of N-acetylcysteine (NAC): the emerging role of H2S and sulfane sulfur species - Pedre, Brandán; Barayeu, Uladzimir; Ezeriņa, Daria; Dick, Tobias P. (Pharmacology & therapeutics, 2021)
Initially adopted as a mucolytic about 60 years ago, the cysteine prodrug N-acetylcysteine (NAC) is the standard of care to treat paracetamol intoxication, and is included on the World Health Organization’s list of essential medicines. Additionally, NAC increasingly became the epitome of an “antioxidant”. Arguably, it is the most widely used “antioxidant” in experimental cell and animal biology, as well as clinical studies. Most investigators use and test NAC with the idea that it prevents or attenuates oxidative stress. Conventionally, it is assumed that NAC acts as (i) a reductant of disulfide bonds, (ii) a scavenger of reactive oxygen species and/or (iii) a precursor for glutathione biosynthesis. While these mechanisms may apply under specific circumstances, they cannot be generalized to explain the effects of NAC in a majority of settings and situations. In most cases the mechanism of action has remained unclear and untested. In this review, we discuss the validity of conventional assumptions and the scope of a newly discovered mechanism of action, namely the conversion of NAC into hydrogen sulfide and sulfane sulfur species. The antioxidative and cytoprotective activities of per- and polysulfides may explain many of the effects that have previously been ascribed to NAC or NAC-derived glutathione.